Linguistic Activism in Short Films on Social Media as an Effort to Promote the Javanese Language in The Digital Era - Tri Santoso; Hari Kusmanto; Muhammad Syahriandi Adhantoro; Dartim; Duwi Saputro; Nindy Muji Utami (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
The growth of YouTube has created new spaces for the use of the Javanese language as a cultural and political practice. In this context, Javanese emerges as a form of language activism in the digital sphere. This study aims to analyze the forms of Javanese language activism in short films on YouTube. This research employs a qualitative approach. The data sources consist of 10 short films published on YouTube. Data were collected through documentation, transcription, and note-taking techniques. The data analysis follows an interactive model comprising four steps: data collection, data condensation, data display, and conclusion drawing.The findings reveal 14 forms of language activism, including: (1) the use of local language, (2) translanguaging, (3) language as social criticism, (4) language as a medium for health advocacy, (5) strengthening identity and social cohesion, (6) humor, (7) delegitimization of opposing discourse, (8) ritual language, (9) historical narratives, (10) pedagogical activism, (11) language as a tool for mobilization, (12) economic language, (13) criticism of technology use, and (14) symbolic reframing. These findings indicate that social media has become a new ecology for regional language activism. Moreover, it serves as a socio-political arena that enables Javanese to function as an instrument of advocacy, resistance, and identity formation. This study contributes to the development of language activism in digital spaces and offers implications for language preservation policies.   Perkembangan YouTube membuka ruang baru bagi penggunaan bahasa Jawa sebagai praktik kultural dan politis. Dalam konteks ini, bahasa Jawa hadir sebagai bentuk aktivisme di ruang digital. Studi ini bertujuan menganalisis bentuk-bentuk aktivisme bahasa Jawa dalam film pendek di YouTube. Jenis penelitian yang digunakan adalah kualitatif. Sumber data dalam penelitian ini adalah 10 film pendek yang dipublikasikan di YouTube. Pengumpulan data penelitian ini dilakukan dengan metode dokumentasi, transkripsi, dan dilanjutkan teknik catat. Analisis data penelitian ini menggunakan metode interaktif yang meliputi empat langkah, yakni pengumpulan data, kondensasi data, penyajian data, dan penarikan simpulan. Hasil penelitian ini menemukan 14 bentuk aktivisme bahasa. Kelima belas bentuk aktivisme tersebut meliputi: 1) penggunaan bahasa daerah, 2) translanguaging, 3) bahasa sebagai kritik sosial, 4) bahasa sebagai medium advokasi kesehatan, 5) penguatan identitas dan kohesi sosial, 6) humor, 7) delegetimasi wacana lawan, 8) bahasa ritual, 9) narasi sejarah, 10) aktivisme pedagogis, 11) bahasa sebagai alat mobilisasi, 12) bahasa ekonomi, 13) kritik terhadap penggunaan teknologi, dan 14) reframing simbol. Temuan ini menunjukkan bahwa media sosial menjadi ekologi baru dalam upaya aktivisme bahasa daerah. Selain itu, menjadi arena politik-kultural yang memungkinkan bahasa Jawa sebagai instrumen advokasi, perlawanan, dan penguatan identitas. Studi ini berimplikasi dalam pengembangan aktivisme bahasa di ruang digital dan memberikan kontribusi pada kebijakan pelestarian bahasa.